CCNP security secure 642-637 quick reference - Mason, Andrew (Cisco Press, 2011)
<Lt;lt;p>gt;gt;As a final exam preparation tool, the <lt;lt;i>gt;gt;CCNP Security SECURE 642637 Quick Reference<lt;lt;/i>gt;gt; provides a concise review of all objectives on the new CCNP Security SECURE exam (642-637). This eBook provides you with detailed, graphical-based information, highlighting only the key topics in cram-style format.<lt;lt;/p>gt;gt; <lt;lt;p>gt;gt;With this document as your guide, you will review topics on layer 2 security, Network Address Translation (NAT), Cisco IOS firewall, Cisco IOS IPS, VPNs, and Cisco network foundation protection. This fact-filled Quick Reference allows you to get all-important information at a glance, helping you to focus your study on areas of weakness and to enhance memory retention of essential exam concepts.<lt;lt;/p>gt;gt.
Resource description page (viewed Mar. 14, 2011)
Keywords: Computer networks -- Security measures; Firewalls (Computer security); Réseaux d'ordinateurs; Sécurité; Mesures; Coupe-feu (Sécurité informatique); Computer networks; Security measures; Electronic resource